Management of student discipline formation through a social learning approach - Darti Hapsary; Edhy Rustan; Hilal Mahmud (At Turots: Jurnal Pendidikan Islam, 2024)
The research aims is to determine: 1) The condition of students' disciplinary character at Noling Education Foundation Junior High School; 2) The management of implementing student discipline formation through social learning approach at Noling Education Foundation Junior High School. The type of this research is descriptive qualitative research, data collection is conducted through observation, interviews, and documentation methods. As for the data analysis techniques used, they are data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate that 1) The disciplinary character of students at Noling YPN Junior High School has fulfilled 5 indicators of discipline, namely attending school, participating in learning activities, completing assignments, studying at home, and adhering to school regulations properly. There are 2 indicators that show minimal results in shaping student discipline using the social learning approach, namely students' discipline in completing assigned tasks and students' discipline in studying at home. 2) The implementation of student discipline formation management through the social learning approach starts from planning, including formulating objectives, drafting the format of student discipline formation, and establishing school regulations. This process involves Teachers and Education Personnel, School Committees, Stakeholders, and students' parents, considering the goals to be achieved. Teachers apply social learning indicators in the teaching process, and evaluations are conducted to identify the core of teachers' mistakes in shaping student discipline, thus identifying supporting and inhibiting factors, including funding solely sourced from the School Operational Assistance (Bos) funds and the completeness of facilities and infrastructure at Noling YPN Junior High School. 3) The model of student discipline formation consists of regular habits, providing explanations about the rules, explaining the consequences of actions logically, shaping behavior in one step, and teaching problem-solving skills, primarily in shaping student discipline.